Pengaruh Dana Syirkah Temporer dan Usia Dewan Direksi terhadap Profitabilitas Bank Syariah Indonesia, Bank Muamalah Indonesia, Bank Mega Syariah dan Bank BCA Syariah Periode 2021-2023 - Manaf, Abdul; Abadi, Yudha Budi; Wimbawani, Wiwik (Jurnal Ekonomi Syariah dan Pariwisata Halal, 2025)
Profitability is the final result and goal of a company's establishment. A company that has a high profitability value means that the company is successful in running its business operations. Many factors affect profitability, from Corporate Governance factors to Financial Factors. This research method is quantitative descriptive with the object of research being 4 large Islamic banks in Indonesia. The data analysis technique is panel data regression using eviews. The tests used are model selection tests, classical assumption tests and hypothesis tests. The results of this study are the coefficient value and negative t statistic and the probability value of 0.0045 <0.05 meaning that the age of the board of directors has a negative effect on the profitability of Islamic banks and the coefficient value is positive and the probability of 0.0007 <0.05 meaning that Temporary Syirkah Funds have a positive effect on Profitability. The probability value of f-statistics is 0.005 <0.05 meaning that simultaneously Temporary Syirkah funds and the age of the board of directors have an effect on profitability, the results of the R2 test show that both variables are able to give an effect of 72.4% on profitability. The limitations of the study are in the relatively few research objects, but it is considered capable of describing the actual conditions.